A comparison of characteristics and outcomes of patients admitted to the ICU with asthma in Australia and New Zealand and United states. (2nd April 2020) - Abdelkarim, Hussam; Durie, Matthew; Bellomo, Rinaldo; Bergmeir, Christoph; Badawi, Omar; El-Khawas, Khaled; Pilcher, David
Abstract: Objective : To compare the characteristics, use of invasive ventilation and outcomes of patients admitted with critical asthma syndrome (CAS) to ICUs in Australia and New Zealand (ANZ), and a large cohort of ICUs in the United States (US). Methods : We examined two large databases of ICU for patients admitted with CAS in 2014 and 2015. We obtained, analyzed, and compared information on demographic and physiological characteristics, use of invasive mechanical ventilation, and clinical outcome and derived predictive models. Results : Overall, 2202 and 762 patients were admitted with a primary diagnosis of CAS in the ANZ and US databases respectively (0.73% vs. 0.46% of all ICU admissions, P  < 0.001). A similar percentage of patients received invasive mechanical ventilation in the first 24 h (24.7% vs. 24.4%, P  = 0.87) but ANZ patients had lower respiratory rates and higher PaCO2 levels. Overall mortality was low (1.23 for ANZ and 1.71 for USA; P  = 0.36) and even among invasively ventilated patients (2.4% for ANZ vs. 1.1% for USA; P  = 0.38). However, ANZ patients also had longer length of stay in ICU (43 vs. 37 h, P  = 0.001) and hospital (105 vs. 78 h, P  = 0.003). Conclusions : Patients admitted to ANZ and USA ICU with CAS are broadly similar and have a low and similar rate of invasive ventilation and mortality. However, ANZ patients made up a greater proportion of ICU patients and had longer ICU and hospital stays. These findings provide a modern invasive ventilation and mortality rates benchmark for future studies of CAS.